Vacuum sealing drainage therapy in the presence of an external fixation device: A case report. Issue 46 (November 2016) - Sun, Dahui; Ju, Weina; Wang, Tiejun; Yu, Tiecheng; Qi, Baochang
Abstract: Rationale: Vacuum sealing drainage (VSD) is widely utilized for treating traumatic wounds. Patient concerns: It is particularly difficult and time consuming to use in combination with an external fixator. Diagnoses: This is because the hardware or pins used for fixation interfere with maintaining a seal, resulting in poor adhesion and subsequent air leakage. Interventions: To resolve this problem, we have devised a new method for sealing the wound dressing, while maintaining the required vacuum.When using this technique, a rubber strip is wrapped around each pin in 3 circles outside the plastic drape, and then tightly tied. Outcomes: After completing this procedure, a vacuum is obtained, and any air leakage stops. We employed this technique to treat a cohort of patients in our department over a period of two years, and obtained good healing of soft tissue without air leakage, as well as good clinical outcomes. Lessons: We have observed that patients treated with this method experienced good clinical outcomes without air leakage, and we recommend its use in treating cases where an external fixation device is present.